Impacto da Pandemia na Discussão sobre Saúde Mental: O Caso do Discord no Brasil - Bento, Pedro; Buzelin, Arthur; Aquino, Yan; Carvalho, Isis; Dutenhefner, Pedro; Dayrell, Lucas; Santana, Caio; Estanislau, Victoria; Pappa, Gisele L.; Miranda, Debora; Almeida, Virgilio; Meira Jr, Wagner (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2024: Proceedings of the 30th Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2024.243238, 2024)
The period of social isolation due to COVID-19 generated a significant impact on our routines, relationships, and mental health. We had to suddenly adapt to a new scenario where social interactions were only possible online, resulting in increased use of various platforms, including Discord. Given the popularization of this platform in the past years, this paper analyzes data from public Brazilian Discord groups before, during and after the pandemic, focusing on topics related to users’ mental health. We conduct a network characterization, observing how the distribution of the number of messages and active users changed over time. We then analyze the content of messages based on a set of keywords selected by psychiatric specialists and divided into six categories: Depression, Suicide, Anxiety, Psychosis, Disorders, and General Issues. Our analyses showed a peak of activity at the beginning of 2020, coinciding with quarantine measures in Brazil. During the pandemic, we also observed an increase in activity during atypical hours, such as from 3 a.m. to 9 a.m. With the end of the pandemic, the message exchange rates returned to normal, but user retention remained high compared to the pre-pandemic period. Regarding the content of messages, we noticed that, during isolation, there was a higher frequency in the use of sensitive terms, which remained elevated even after the end of the pandemic.